A Systematic Review of Shariah-Compliant Hedging: Foundations, Instruments, Practices, and Challenges - Hernawaty (Jurnal Ilmiah Manajemen Kesatuan, 2025)
Islamic finance has grown significantly, creating a demand for risk management tools that comply with religious principles prohibiting interest, excessive uncertainty, and gambling. This study aims to review the concepts, instruments, practices, and challenges of Shariah-compliant hedging to understand its alignment with Islamic principles and market needs. A systematic literature review was conducted, analyzing 25 publications from 2015 to 2025, including a comprehensive literature review to identify theoretical foundations, instrument designs, and implementation gaps. The findings reveal that instruments like unilateral promise-based forwards, commodity trade-based swaps, forward sales, manufacturing contracts, and earnest money contracts enable risk management but face challenges such as high transaction costs and regulatory disparities. This review uniquely synthesizes theoretical and practical insights, highlighting tensions between Shariah authenticity and economic efficiency. Despite progress, issues like form-over-substance criticisms and lack of standardized regulations persist, limiting market accessibility. The study concludes that Shariah-compliant hedging is viable but requires innovation in instrument design and regulatory harmonization to balance ethical compliance with financial competitiveness, offering valuable insights for practitioners and policymakers seeking to advance Islamic risk management.